Prevention of chemotherapy drug-mediated human hair follicle damage: combined use of cooling with antioxidant suppresses oxidative stress and prevents matrix keratinocyte cytotoxicity - Ibraheem, Khalidah; Smith, Adrian; Collett, Andrew; Georgopoulos, Nikolaos T. (Frontiers in Pharmacology, 2025)
BackgroundChemotherapy-induced alopecia (CIA) is a distressing side-effect of cancer treatment. Scalp cooling remains the only available method to mitigate CIA, but its effectiveness varies amongst patients. We previously reported that the cytoprotective effects of cooling are temperature dependent. Here we investigated whether blockade of reactive oxygen species (ROS) by antioxidants can potentiate cooling-mediated cytoprotection against chemotherapy-induced damage in human keratinocytes and hair follicles (HFs).MethodsIn vitro monocultures of keratinocytes and ex vivo HF organ cultures were treated with doxorubicin or 4-hydroxycyclophosphamide (4HC). Cooling conditions tested ranged between 18°C and 26°C. Keratinocyte viability was assessed via MTS assays. HF viability and function were evaluated by hair shaft elongation measurements, hair cycle staging, immunolabelling for proliferation (% Ki-67+ cells) and apoptosis (% TUNEL+ cells), and melanin intensity via histomorphometry. ROS levels were quantified by flow cytometry and spectrophotometrically. The effects of a panel of antioxidants in combination with cooling were assessed.ResultsChemotherapy agents reduced keratinocyte viability at 37°C by ∼65%–70%, induced HF dystrophy evident by decreased proliferation (9% Ki-67+ cells), increased apoptosis (23% TUNEL+ cells), and reduced anagen (∼10%) and pigmentation. Optimal cooling at 18°C rescued cell viability, significantly (p < 0.001) restored HF proliferation (42% Ki-67+ cells) and pigmentation, suppressed apoptosis (10% TUNEL+ cells), restored anagen (∼70%) and induced a 2-3-fold increase in hair shaft elongation (p < 0.001), whereas cooling at 26°C was only partially effective. ROS generation increased >3-fold following drug exposure and was attenuated by cooling in a temperature-dependent fashion (p < 0.001). Co-treatment with antioxidant (such as N-acetylcysteine) at 26°C restored cell viability to levels comparable with 18°C, normalizing HF proliferation (41% Ki-67+ cells), suppressing apoptosis (8% TUNEL+ cells) and restoring HF function (e.g., hair shaft elongation, p < 0.001).ConclusionCooling effectively suppresses chemotherapy drug-induced cytotoxicity in human keratinocytes and HFs in a temperature-dependent manner. Combination of cooling with antioxidant functionally compensates for inadequate cytoprotection under sub-optimal cooling conditions, as it prevents HF cell apoptosis and maintains HF viability (proliferation) and functionality (hair growth). This combinatorial approach holds translational promise for improving the efficacy and consistency of scalp cooling in preventing CIA, ultimately improving cancer patient quality-of-life during chemotherapy treatment.